4 and 5 Year Old Children's Perception of Facebook - Rita Brito (Yeni Medya)
The aim of this article is to analyze and describe the perceptions of children with 4 and 5 years old regarding the use of Facebook. For this purpose, 33 children were interviewed. From the data analysis it was found that most children know Facebook, mentioning that it is possible to communicate, play games and view photos on the social network. In addition to these representations, some children also mentioned that they used Facebook to communicate with their family or to play games. The representations mentioned by children are based primarily on the observation of their parents using Facebook. From these findings, it is proposed that school could provide training to parents and children about issues of online safety, in order to prepare both for a conscientious use of social networks.